The Role of Human Resources in Civil Engineering Infrastructure Development: A Literature Review - FA. Luky Primantari; Silvia Yulita Ratih Setyo Rahayu; Zandra Dwanita Widodo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Civil engineering infrastructure development plays a vital role in driving economic progress and enhancing the quality of life within communities. The success of infrastructure projects depends not only on budgetary and technological factors but also on the quality of human resources (HR) involved in every project phase, from planning to maintenance. This literature review highlights that skilled and competent HR is a critical factor in achieving project success, particularly amidst increasing complexity and the challenges posed by globalization. Key issues faced by the sector include a shortage of skilled labor, high turnover rates, and a misalignment between educational outcomes and the skills required in the field. Additionally, technological advancements, such as the adoption of Building Information Modeling (BIM) and Artificial Intelligence (AI), demand continuous skill enhancement to adapt to the growing automation of industry processes. Effective HR management—encompassing ongoing education, fair incentive systems, and the integration of technology into HR practices—is essential for boosting productivity and mitigating risks during project execution. A comprehensive approach, including a structured HR management system, is required to ensure the sustainability and quality of infrastructure development. This study aims to provide an in-depth understanding of the critical role of HR management in the civil engineering sector and proposes practical recommendations for improving HR quality to meet the evolving demands of the construction industry.